Description of clean and healthy lifestyle behaviour implementation in MI Ma’arif Gandrungmanis Cilacap students during the pandemic time Covid-19 - Miftah, Cahya Rahma; Sunarto, Sunarto (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Clean and healthy living behaviour (PHBS) in elementary school (SD) children, in the age range of about 10 years, is often discussed because it is associated with active physical activity. Objective: To describe the developments in PHBS during the COVID-19 pandemic in elementary school children Methods: This study used a quantitative descriptive design with a survey method using a questionnaire to determine the description of PHBS implementation in 4th, 5th, and 6th-grade students of MI Ma’arif Gandrungmanis. The data was obtained by identifying students’ behaviour regarding PHBS towards health protocols during the Covid-19 pandemic in schools. Results: The results of this study show an overview of the PHBS of MI Ma’arif Gandrungmanis students during the Covid-19 pandemic with a very good category of 7.8%, good category of 28.4%, fairly good category of 37.1%, less good category of 20.7%, and not good category 6%. Conclusion: The PHBS in 4th, 5th, and 6th-grade of MI Ma’arif Gandrungmanis is mostly in the fairly good category with a percentage of 37.1%.